A new species of Allogamasellus Athias-Henriot (Acari: Mesostigmata: Ologamasidae) from Iran. Issue 3 (2nd April 2016) - Nemati, Alireza; Vatankhah, Farzaneh
ABSTRACT: Allogamasellus castilhoi sp. nov . (Mesostigmata: Ologamasidae) is described based on the morphology of adult females collected from nest of Formica sp. (Hymenoptera: Formicidae) at Shahrekord region, Chaharmahal va Bakhtiari province, Iran. The key for the separation of adult females of the three recognizable world species of Allogamasellus is provided.